2006
DOI: 10.1007/s10654-006-9016-y
|View full text |Cite
|
Sign up to set email alerts
|

Intra-familial Transmission of Helicobacter pylori Infection in Children of Households with Multiple Generations in Vietnam

Abstract: This community-based cross-sectional study in 533 participants from 135 households with multiple generations living in the same household aimed at investigating the relationship between Helicobacter pylori infection in children and the other household members. H. pylori infection in children was found significantly associated with the infection in mothers [OR (95% CI): 2.50 (1.19-5.26)], even after being adjusted for sex, age group and sibling number [adjusted OR (95% CI): 2.47 (1.12-5.47)]. It was also signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 39 publications
7
22
1
Order By: Relevance
“…H. pylori seroprevalence was 52.1% in adults and 42.8% in children ≤18 years old. Our findings are comparable to those reported in other community-based studies in Vietnam [10][11][12][13][14][15]. In one community-based study carried out in Kinh majority ethnic, using the same serological test, Hoang et al found an overall seroprevalence of H. pylori of 58.2% with 47.3% in children [10].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…H. pylori seroprevalence was 52.1% in adults and 42.8% in children ≤18 years old. Our findings are comparable to those reported in other community-based studies in Vietnam [10][11][12][13][14][15]. In one community-based study carried out in Kinh majority ethnic, using the same serological test, Hoang et al found an overall seroprevalence of H. pylori of 58.2% with 47.3% in children [10].…”
Section: Discussionsupporting
confidence: 88%
“…Vietnam is also home to 54 ethnic groups with different cultures, of which 75% to 80% are living in rural or remote areas [8,9]. High rates of H. pylori infection were reported in both hospital-based and community-based studies from Vietnam [10][11][12][13]. Different risk factors for H. pylori infection have been identified in the Kinh ethnic majority [10][11][12] and among ethnic minorities [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, crowded living conditions and high population density are associated with increased rates of microbial transmission, and similar conditions would be expected to increase intrafamilial spread. H. pylori acquisition, for example, is enhanced under such conditions (Cervantes et al 2010, Ford et al 2007, Goodman et al 2005, Goodman & Correa 2000, Nguyen et al 2006.…”
Section: Vertical and Horizontal Transmissionmentioning
confidence: 99%